The Role of Market Orientation, Financial Competence, Government Support For SME’s Innovation and Competitiveness - Purnamasari, Dian Indri; Irawati, Fefra; Budiarto, Dekeng Setyo (Jurnal Akuntansi dan Bisnis, 2023)
The Covid-19 pandemic that has attacked all countries has made various businesses suffer losses, especially small businesses. Small businesses need the right strategy to be competitive in the market. This study will examine whether market orientation, financial competence, government support, and innovation are antecedents of the competitiveness of SMEs. This study uses 124 SMEs owners as research respondents. Questionnaires were administered offline and online and analyzed using Smart PLS to prove the hypothesis. The results show that the roles of market orientation, financial competence, government support, and innovation are the antecedents of innovation. This research has implications for the government to provide full support to SMEs owners to survive in the face of environmental uncertainty. Pandemi Covid-19 yang menyerang semua negara membuat berbagai bisnis mengalami kerugian, terutama usaha kecil. Usaha kecil membutuhkan strategi yang tepat untuk dapat bersaing di pasar. Studi ini akan mengkaji apakah orientasi pasar, kompetensi keuangan, dukungan pemerintah, dan inovasi merupakan anteseden dari daya saing UKM. Penelitian ini menggunakan 124 pemilik UKM sebagai responden penelitian. Kuesioner diberikan secara offline dan online yang dianalisis menggunakan Smart PLS untuk membuktikan hipotesis. Hasil penelitian menunjukkan bahwa peran orientasi pasar, kompetensi finansial, dukungan pemerintah, dan inovasi merupakan anteseden inovasi. Penelitian ini memberikan implikasi kepada pemerintah untuk mendukungan penuh pemilik UKM agar mampu bertahan dalam menghadapi ketidakpastian lingkungan.